An Introduction to banking : liquidity risk and asset-liability - Choudhry, Moorad (Chichester, England : John Wiley & Son, Inc., 2011)
This book introduces the key concepts of banking, concentrating on the application
1. Bank and business capital -- 2. The money markets -- 3. The yield curve -- 4. Introduction to trading and hedging -- 5. Asset and liability management I -- 6. Asset and liability management II -- 7. Asset and liability management III -- 8. Bank liquidity risk management -- 9. A sustainable bank business model: capital, liquidity and leverage -- 10. Bank regulatory capital
Includes bibliographical references.
Keywords: ASSET-LIABILITY MANAGEMENT